2017
DOI: 10.1134/s0006297917130090
|View full text |Cite
|
Sign up to set email alerts
|

Three-finger proteins from the Ly6/uPAR family: Functional diversity within one structural motif

Abstract: The discovery in higher animals of proteins from the Ly6/uPAR family, which have structural homology with snake "three-finger" neurotoxins, has generated great interest in these molecules and their role in the functioning of the organism. These proteins have been found in the nervous, immune, endocrine, and reproductive systems of mammals. There are two types of the Ly6/uPAR proteins: those associated with the cell membrane by GPI-anchor and secreted ones. For some of them (Lynx1, SLURP-1, SLURP-2, Lypd6), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 82 publications
1
58
0
Order By: Relevance
“…Higher animals produce endogenous proteins from the Ly6/uPAR family, which share structural homology with snake α‐neurotoxins acting on nicotinic acetylcholine receptors (nAChRs) (Loughner et al ., ; Vasilyeva et al ., ). Some of these proteins, such as Lynx1 and Lypd6 in the brain, are membrane‐tethered, whereas others such as the secreted Ly6/uPAR proteins SLURP‐1 and SLURP‐2, are secreted by epithelial tissues and probably involved in the development of a number of skin diseases including Mal de Meleda (Allan et al ., ; Perez and Khachemoune, ) and psoriasis (Tsuji et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Higher animals produce endogenous proteins from the Ly6/uPAR family, which share structural homology with snake α‐neurotoxins acting on nicotinic acetylcholine receptors (nAChRs) (Loughner et al ., ; Vasilyeva et al ., ). Some of these proteins, such as Lynx1 and Lypd6 in the brain, are membrane‐tethered, whereas others such as the secreted Ly6/uPAR proteins SLURP‐1 and SLURP‐2, are secreted by epithelial tissues and probably involved in the development of a number of skin diseases including Mal de Meleda (Allan et al ., ; Perez and Khachemoune, ) and psoriasis (Tsuji et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Ly-6/uPAR proteins or ‘three-finger’ proteins (TFPs) contain characteristic ‘three-finger’ domain(s) or LU-domain(s) [ 1 ]. Each LU-domain is composed of a compact disulfide-stabilized β-structural core (‘head’) and three protruding loops (‘fingers’).…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the evolutionary relationships between Tfps1‐6 (GeneBank accession No: Tfp1 [CD59]—MK060020; Tfp2—MK060015; Tfp3—MK060016; Tfp4—MK060017; Tfp5—MK060018; Tfp6—MK060019), that we have identified in X. laevis , and Prod1, CD59, and Lypd6, we have performed the alignment and clustering analyses with these proteins from different species. First, the alignment demonstrated the presence in Tfp4 protein of all conserved cysteines, crucial for the functioning of the three‐fingers proteins (Vasilyeva, Loktyushov, Bychkov, Shenkarev, & Lyukmanova, ) (Figure a). Second, clustering of Tfp1‐6 with Prod1, CD59 and Lypd6 revealed that different Tfps cluster with different members of the CD59/lypd6 superfamily (Figure b).…”
Section: Resultsmentioning
confidence: 99%